Prostaglandin E Receptor 4 Antagonist in Cancer Immunotherapy: Mechanisms of Action - Take, Yukinori; Koizumi, Shinichi; Nagahisa, Atsushi (Frontiers in Immunology, 2020)
A highly-expressed prostaglandin E2 (PGE2) in tumor tissues suppresses antitumor immunity in the tumor microenvironment (TME) and causes tumor immune evasion leading to disease progression. In animal studies, selective inhibition of the prostaglandin E receptor 4 (EP4), one of four PGE2 receptors, suppresses tumor growth, restoring the tumor immune response toward an antitumorigenic condition. This review summarizes PGE2/EP4 signal inhibition in relation to the Cancer-Immunity Cycle (C-IC), which describes fundamental tumor-immune interactions in cancer immunotherapy. PGE2 is suggested to slowdown C-IC by inhibiting natural killer (NK) cell functions, suppressing the supply of conventional dendritic cell (cDC) precursors to the TME. This is critical for the tumor-associated antigen priming of CD8+ T cells and their translocation to the tumor tissue from the tumor-draining lymph node. Furthermore, PGE2 activates several key immune-suppressive cells present in tumors and counteracts tumoricidal properties of the effector CD8+ T cells. These effects of PGE2 drive the tumors to non-T cell-inflamed tumors and cause refractory conditions to cancer immunotherapies, e.g., immune checkpoint inhibitor (ICI) treatment. EP4 antagonist therapy is suggested to inhibit the immune-suppressive and tumorigenic roles of PGE2 in tumors, and it may sensitize the therapeutic effects of ICIs in patients with non-inflamed and C-IC-deficient tumors. This review provides insight into the mechanism of action of EP4 antagonists in cancer immunotherapy and suggests a C-IC modulating opportunity for EP4 antagonist therapy in combination with ICIs and/or other cancer therapies.